Laparoscopic Versus Open Colectomy for Colorectal Cancer: Postoperative Outcomes—A Systematic Review (The Review of Diabetic Studies, 2025)
Background: Colorectal cancer (CRC) remains a major global health burden, with colectomy being the cornerstone of curative treatment. The evolution from open colectomy (OC) to laparoscopic colectomy (LC) has aimed to minimize surgical trauma, improve recovery, and preserve oncologic efficacy. This systematic review synthesizes evidence comparing postoperative and oncologic outcomes between LC and OC in CRC management.Methods: Following PRISMA 2020 guidelines, ten clinical studies published between 2002 and 2025—including randomized controlled trials (RCTs) and meta-analyses—were analyzed. Databases searched included PubMed, Scopus, Web of Science, Embase, and Google Scholar. Outcomes assessed comprised operative time, complication rates, postoperative pain, recovery indices, hospital stay, and long-term survival (DFS and OS). Methodological quality was evaluated using the Cochrane RoB 2 and Newcastle–Ottawa Scale (NOS).ResultsAcross studies, LC demonstrated significantly shorter hospital stays (2–3 days), reduced postoperative pain (p < 0.05), and faster bowel recovery compared with OC. Oncologic outcomes—including lymph node harvest, DFS, and OS—were comparable, indicating oncologic non-inferiority. Meta-analyses confirmed consistent advantages in short-term recovery without compromising long-term survival. However, benefits were attenuated in advanced T4 or emergency cases, where technical complexity limited LC feasibility.Conclusion: Laparoscopic colectomy offers superior short-term recovery outcomes with equivalent oncologic safety compared to open colectomy. Its implementation in advanced and emergent cases remains surgeon- and institution-dependent, requiring further standardization and skill optimization.